Answer:
Explanation:
The standard form of an equation is expressed as y = mx+b
m is the slope
Given the equation x - y = 6
Rewrite in standard form;
-y = -x + 6
Multiply through by -1
-(-y) = -(-x) - 6
y = x - 6
Compare with the standard equation
mx = 1x
mx+b
m is the slope
Given
Answer:
6/1
Step-by-step explanation:
Answer:
yes
Step-by-step explanation:
The line intersects each parabola in one point, so is tangent to both.
__
For the first parabola, the point of intersection is ...
y^2 = 4(-y-1)
y^2 +4y +4 = 0
(y+2)^2 = 0
y = -2 . . . . . . . . one solution only
x = -(-2)-1 = 1
The point of intersection is (1, -2).
__
For the second parabola, the equation is the same, but with x and y interchanged:
x^2 = 4(-x-1)
(x +2)^2 = 0
x = -2, y = 1 . . . . . one point of intersection only
___
If the line is not parallel to the axis of symmetry, it is tangent if there is only one point of intersection. Here the line x+y+1=0 is tangent to both y^2=4x and x^2=4y.
_____
Another way to consider this is to look at the two parabolas as mirror images of each other across the line y=x. The given line is perpendicular to that line of reflection, so if it is tangent to one parabola, it is tangent to both.
The perpendicular line to x-6y=2, and passing through (2, 4) is y=-6x+16
Answer:
6x - 2(x - 3) and x + 3(x - 2) - 6
The two expresaions that are quivalent are <u>6x - 2(x - 3)</u> and <u>x + 3(x - 2) - 6</u>.
Step-by-step explanation:
First expression which is 4(x - 3) is an example of a binomial that when multiplied together, the product would be 4x - 12. Therefore, second and third expressions are the answer.
#CarryOnLearning
#BrainliestBunch
#LetsStudy
#AnswerForTrees
#BrainlyFast
#BuwanNgWikaSaBrainly